A call to establish a child-centred disaster management framework in Zimbabwe - Sillah, Ramphal M. (AOSIS, 2021)
Disasters have increased in intensity and frequency in recent times. However, disasters do not affect all groups in a society in a similar manner. This article, based mainly on qualitative desk research and document analysis, aims to illuminate the specific vulnerability of children to hazards and disasters. The research showed that owing to their special physiological, psychological, emotional and economic stature, children are an inherently vulnerable group. The paper advocates for existing disaster management structures and systems in Zimbabwe to elevate reduction of disaster risk amongst children within the scope of child protection, which aims to create a protective environment that shelters children from any form of harm or abuse. The paper proffers recommendations on how to design disaster management programmes in Zimbabwe with the needs of children in mind.